Nutrient and Coliform Levels in the Surface Waters of a Protected Upland Lake in Ormoc City Philippines - Eugie V. Cinco; Cherryhel B. Toralde; Olga G. Corales-Ultra; Rolly G. Fuentes (Environment and Natural Resources Journal)
Lake Danao in OrmocCity, Philippines, is a legally protected freshwater ecosystem classified as a Class A water body by the government. However, its ecosystem services and biological stability are continuously threatened by untreated runoff from human activities in the upland regions surrounding the lake. A study was thus conducted to evaluate the water quality of Lake Danao using water quality indices and microbiological assessments. Water samples were collected in five sampling stations from April 2021 to June 2022. Results ranged between 0 and 20.53 mg/L for nitrates, 0 and 1.06 mg/L for nitrites, 0.07 and 2.5 mg/L for phosphates, 2.86 and 7.73 mg/L for dissolved oxygen, and 2.83 and 1,600 MPN/100 mLfor total coliform. On average, the readings of these parameters were above the Philippines’ Department of Environment and Natural Resources maximum allowable limits for Class A waters. In addition, fecal coliform (0-849.67 MPN/100 mL, x̄=40.17 MPN/100 mL) consistently exceeded the limit. Mean readings in fecal coliform and phosphate levels were drawing near Class B levels. The results may impose possible threats to human health, as high levels of coliform suggest that the lake is already an unsafe source of potable water.In addition, fluctuations across sampling periods were observed for all parameters measured, except for total and fecal coliforms. Lastly, heavy precipitation resulted in a very low N/P ratio (<1) which suggests that the possible source of the phosphate is anthropogenic, and runoff from the surrounding land hascarried significant concentrations of phosphates and coliform into the water body. The nutrient pollution index shows that Lake Danao is “moderately polluted,” while its trophic state indexstates that it is “mesotrophic.” It is recommended that strategies in runoff treatment should be advanced, be it by nature-based solutions, such as ensuring thick vegetation cover along the buffer zone, or via man-made interventions like no-till farming. Regular monitoring of the lake water quality should therefore be continued, particularly for nutrients and coliform, to ensure the maintenance, protection, and responsible use of the protected upland lake.